The determinants of perinatal mortality in a teaching group of hospitals in Southern Africa - Knutzen, Victor Keith (Department of Medicine, 2020)
Icebergs - Why start a thesis thinking about icebergs? Death from medical conditions represents the tip of an iceberg. What causes death in some, will maim, injure or leave damaged in others. Death remains a parameter with which to measure part of the effect of a disorder on the mother or fetus. What will prevent mortality will prevent morbidity and it is largely towards the prevention of the latter that modern medicine is aimed.